Re-evaluating Multifactor Leadership Questionnaire Construct: A Validation Study in the Pharmaceutical Sector of Punjab, Pakistan Context - Imam, Talha; Tyasari, Irma; Pahi, Munwar Hussain (Jurnal Ekonomi Modernisasi, 2017)
Current study inspected the psychometric properties of multifactor leadership questionnaire (MLQ) in pharmaceutical sector of Pakistan. Data was collected from 370 employees working in pharmaceutical companies in Lahore region of Punjab, Pakistan. Data was analyzed by using Smart-PLS 2.0 M3 statistical software. The results of the current study demonstrated that all the leadership styles in MLQ were adequately relevant according to the Pakistani context. The results further revealed that each leadership style showed optimum internal consistency reliability, convergent validity and discriminant validity. Based on the current study results, it is highly suggested that the use of MLQ instrument would be very useful in order to measure the leadership styles in Pakistan, particularly in pharmaceutical sector.